At odds with each other: development and environmental sustainability in Cecil Rajendra's selected poems - Fadzil, Suhada; Zainal, Zainor Izat (Universiti Putra Malaysia Press, 2018)
Development has always been Malaysia’s priority since independence in 1957. This enthusiasm is reflected in many of the country’s past and existing policies and plans. Being one of the countries endowed with plenty of natural resources, Malaysia’s rapid capitalist driven development has, however, taken its tolls on nature, causing concern that environmental sustainability is taken for granted. The antagonistic relations between development and environmental sustainability have also preoccupied local writers writing in English, such as Muhammad Haji Salleh, KS Maniam and Cecil Rajendra, to name a few. Among these writers, Rajendra is the most consistent in writing about environmental issues. This study analyses Cecil Rajendra’s selected poems, ranging from 1978 to 2004. It deals with the questions of how Rajendra characterises development in Malaysia and what this conveys about Rajendra’s view on environmental sustainability. Marxist concepts of treadmill of production and metabolic rift are applied to examine the antagonistic relations between development and environmental sustainability. This paper extends the literary critical practice of Malaysian poetry in English by focusing on the environmental perspective, adding to the debate on development in Malaysia.